2022
DOI: 10.1155/2022/4076426
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reaction and Generalized Heat Flux Model for Powell–Eyring Model with Radiation Effects

Abstract: In the current research, the numerical solutions for heat transfer in an Eyring–Powell fluid that conducts electricity past an exponentially growing sheet with chemical reactions are examined. As the sheet is stretched in the x direction, the flow occupies the region   y > 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The formation other than the non-Newtonian fluids, this model has few benefits as of simple calculation and physical vigor. Salah et al 1 discussed the effects of chemical reaction for a generalized heat flux model for Eyring-Powell fluid along with the effect of the radiation. The effects of radiation and chemical reaction on unsteady Eyring-Powell nanofluid flow over a moving surface are disused by Taraka ramu and Narayana 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The formation other than the non-Newtonian fluids, this model has few benefits as of simple calculation and physical vigor. Salah et al 1 discussed the effects of chemical reaction for a generalized heat flux model for Eyring-Powell fluid along with the effect of the radiation. The effects of radiation and chemical reaction on unsteady Eyring-Powell nanofluid flow over a moving surface are disused by Taraka ramu and Narayana 2 .…”
Section: Introductionmentioning
confidence: 99%
“…By employing the Bvp4c method, Paul and Das (2023) studied a two-dimensional stable issue that integrates the magnetohydrodynamic effect with three separate flows of fluid from the boundary layer across an exponentially stretched sheet under the impact of thermal radiation and chemical reactions. There are some interesting contributions to chemical reactions in the literature (Khan et al, 2022;Salah, 2022;Sidahmed and Salah, 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis revealed that the thermal stratification parameter and Cattaneo-Chiristov time relaxation dampen the distribution of fluid temperature. Salah [8] examined the flow and heat transfer of dissipative and chemically reacting MHD Eyring-Powell fluid past a sheet that stretches in an exponential manner under non-Fourier's model. This examination revealed that the thermal relaxation time and the Eyring-Powell fluid parameter are inversely related to the temperature profile while the Eckert number indicates an increasing effect on the temperature profile.…”
Section: Introductionmentioning
confidence: 99%